An Historic Overview of Biological Response Modifiers as Antiviral Agents - Page S Morahan; Aangelo J Pinto (Canadian Journal of Infectious Diseases)
A wide variety ofimmunomodulators/biological response modifiers (BRMs) has been demonstrated to provide broad spectrum antiviral activity against both RNA and DNA viruses in several animal species. Dramatic decreases in mortality, reduced virus titres in tissues and reduced histopathology can be produced. The antivirally effective agents include microbially derived materials, polyanions, cytokines and chemically diverse small molecular weight chemicals. The greatest protective effects are observed with prophylactic treatment. although early therapeutic treatment can also be effective. Little direct antiviral activity can be observed in vitro. The findings suggest induction by BRMs of antiviral mediators in vivo early in the course of viral pathogenesis, before the virus has become sequestered in a privileged site or too much infectious virus has been produced for natural resistance to have an impact, immunomodulators are pleiotropic in their immunomodulatory effects, and it has been difficult to establish whether one cell type or mediator is critical for the observed broad spectrum antiviral activity. Therefore, the mechanisms of antiviral action of immunomodulators remain unclear for most systems, but probably involve enhancement of natural immune responses. While no unified antiviral mechanism among different immunomodulators has yet emerged, interferon induction remains a major hypothesis.